2016
DOI: 10.3233/jad-150785
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer’s Disease

Abstract: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 25 publications
2
81
1
Order By: Relevance
“…Similar to previous findings [33], we identified a high prevalence of depressive symptoms in SCI. However, in our sample current depressive symptoms were not more prevalent in SCI than in MCI, and were thus not a characteristic specific for SCI patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to previous findings [33], we identified a high prevalence of depressive symptoms in SCI. However, in our sample current depressive symptoms were not more prevalent in SCI than in MCI, and were thus not a characteristic specific for SCI patients.…”
Section: Discussionsupporting
confidence: 80%
“…However, in our sample current depressive symptoms were not more prevalent in SCI than in MCI, and were thus not a characteristic specific for SCI patients. The prevalence of current depressive symptoms in our study (SCI: 13.3%; MCI: 15%) was lower than what was reported in a similar although smaller memory clinic sample by Elfgren et al [11] (SCI: 33%; MCI 27%) and in a similar memory clinic study assessing depressive symptoms by questionnaire [33] (SCI: 45.5%; MCI: 42-50%). It was also lower than the median value of 44.3% depressive symptoms in MCI patients in hospital-based studies [34].…”
Section: Discussioncontrasting
confidence: 54%
“…This confirmed the efficacy of this system, which was designed to alleviate disturbed attention and concentration, and suggests that cognitive impairment was alleviated through increasing attention and concentration. The N-ADL score after the intervention, on the other hand, was shown to be significantly associated with the change in MMSE score, supporting the previous findings [13,14] that cognitive impairment is associated with impaired ADL in dementia. During this intervention program, the subjects were not spoken to, so that their concentration was focused on the task at hand.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, there were no measures of insight or informant concerns included in this study, which could add further information about other factors that might mediate the relationship between SCD and objective cognitive performance. As many previous studies have shown, the influence of depressive symptomatology on subjective, metacognitive monitoring and self-reflective measures cannot be discounted [3, 25, 30]. It is possible that early signs of both depressive symptoms and greater SCD in cognitively-normal older adults may well be indicative of overall ‘illness’ due to a milieu of disease-related effects [31], and thus represent greater risk of progression to dementia.…”
Section: Discussionmentioning
confidence: 99%